Tanggung Jawab Bank Syariah Indonesia Pasca Peristiwa Hacking Yang Merugikan Beberapa Nasabah - M. Shidiq Mukmin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The rapid development of technology is very influential for economic life, especially banking. This can be seen from the use of technology in banking activities such as the use of ATMs and Mobile Banking which facilitate customer transactions. However, this technological development also has a dark side when someone abuses their expertise in technology to do something that violates the law. Such as burglary, hacking, phishing, and so forth. Therefore extra caution is needed in using technology in money circulation activities to reduce the risk of unwanted things happening. If, for example, a bank is hit by a cyberattack and harms customers, who should be responsible for this incident? Is it the bank's board of directors or other organs? In the results of the analysis it was found that if a customer suffers a loss after a cyber attack, the internal organs of the PT are not personally responsible for the loss because it is not the fault of the organs. Customers can make deposit guarantee claims to LPS but with a limit of Rp. 2 billion.